Kähler-Yang-Mills Equations and Vortices - García-Prada, Oscar (Symmetry, Integrability and Geometry: Methods and Applications, 2024)
The Kähler-Yang-Mills equations are coupled equations for a Kähler metric on a compact complex manifold and a connection on a complex vector bundle over it. After briefly reviewing the main aspects of the geometry of the Kähler-Yang-Mills equations, we consider dimensional reductions of the equations related to vortices — solutions to certain Yang-Mills-Higgs equations.